Transitions in Black and Latinx Community-Based Doula Work in the US During COVID-19 - Rivera, Mariel (Frontiers in Sociology, 2021)
In response to COVID-19, many doulas, including community-based doulas (CBDs), have shifted to virtual doula work, placing aspects of doula care online. CBDs typically center Black and Brown mothers and come from the same community as their clients, granting access to doula care for many individuals who would traditionally not have access. Two partner CBD organizations in Central New York—Village Birth International and Doula 4 a Queen—transitioned to virtual doula work, continuing to center Black and Afro-Latinx people. As CBDs began to transition their work online, they had to create new ways to include both the community and doula aspects of their work. My research has captured these doulas’ experiences since mid-2019 and has documented their transition from in-person doula work to virtual work. This also included their experiences of hosting doula trainings that were originally designed to be held in person. To understand this turn to virtual doula work, in this article I draw on social media engagement, online interviews, Zoom discussions, and personal experience to capture how CBD work shifted to virtual platforms can still center Black and Afro-Latinx folks in their communities and beyond.